Pemberdayaan Masyarakat Dalam Pengelolaan Potensi Desa Menuju Daerah Wisata Mandiri Di Desa Koto Benai Kabupaten Kuantan Singingi - Eni Sumiarsih; Kausar Kausar; Eddiwan Eddiwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The purpose of community service activities packaged in the form of mentoring and training is to increase community knowledge in managing village potential in the fields of fisheries, agriculture and home industry to make Koto Benai Tourism Village a tourist area. The method in this service activity consists of lectures and direct practice in the field. This activity was carried out from July to August 2021 in Koto Benai Village, Kutan Singingi Regency. The stages carried out are, socialization, FGD and training as well as mentoring and monitoring. The results of service activities regarding exploring the local potential of the village are an effort to encourage solving problems by looking at the problems in the village community itself. The training provided on environmentally friendly fisheries, as well as counseling in the field of agriculture and training in the home industry. The level of achievement of the PKM program targets can be said to be successful. This can be seen from the results of the pre-test and post-test given to participants. As well as for BUDIKDAMBER fish cultivation, the community can enjoy the kale harvest 2 times a month. The yield of kale is Rp. 120,000 x 3 months is Rp. 360,000 while the yield of catfish: 16 kg x Rp. 20,000 = Rp. 320,000 and a profit of Rp. 160,000 so that this can improve the local community's economy.